An Integrated Approach in COVID-19 Patient with High Oxygen Dependency Status - Satyal, Jaya; khatiwada, Kasi; koju, Pratigya; Adhikari, Jhularam; kc, Pradeep (Annapurna Journal of Health Sciences, 2023)
Covid-19 has become a global pandemic leading towards thousands of death worldwide.It is infectious disease caused by a new corona virus called SARS-cov-2.WHO learned of the new virus on 31 december 2019 for the first time, following a report of cluster of cases of viral pneumonia in Wuhan, China. However, we report a presentation of covid infection in a 45 year old male in a covid hospital where he was treated with integrated approach i.e Allopathy,Ayurveda,TCM(Traditional Chinese Medicine),Yoga and physiotherapy.During treatment Patient was kept on cpap for some days and got discharged after complete treatment.